2022
DOI: 10.3390/molecules27206860
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Silver and Gold Nanoparticles Prepared by Photoreduction Process with Leaves and Fruit Extracts of Plinia cauliflora and Punica granatum

Abstract: The increased number of resistant microbes generates a search for new antibiotic methods. Metallic nanoparticles have emerged as a new platform against several microorganisms. The nanoparticles can damage the bacteria membrane and DNA by oxidative stress. The photoreduction process is a clean and low-cost method for obtaining silver and gold nanoparticles. This work describes two original insights: (1) the use of extracts of leaves and fruits from a Brazilian plant Plinia cauliflora, compared with a well know … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 88 publications
(91 reference statements)
1
15
0
Order By: Relevance
“…Our findings of antibacterial activity revealed that escalating the concentrations of ScAu-NPs increases the zone diameter. Similar findings were observed by other researchers when they examined the antibacterial activity of plant-mediated AuNPs against clinical and American Type Culture Collection (ATCC) strains and concluded substantial antibacterial activity [24,25]. MIC of ScAu-NPs was also calculated to determine the least concentration that inhibits the growth of uropathogens.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings of antibacterial activity revealed that escalating the concentrations of ScAu-NPs increases the zone diameter. Similar findings were observed by other researchers when they examined the antibacterial activity of plant-mediated AuNPs against clinical and American Type Culture Collection (ATCC) strains and concluded substantial antibacterial activity [24,25]. MIC of ScAu-NPs was also calculated to determine the least concentration that inhibits the growth of uropathogens.…”
Section: Discussionsupporting
confidence: 78%
“…Intensive bands at 1602 and 1616 cm −1 were observed in the FTIR spectra of SVE and FUE, respectively. This broad band in the 1600 and 1700 cm −1 region could be attributed to the C=C stretching vibration of aromatic rings, as well as the C=O group of amides, esters, or C=O group on the C ring of flavones [ 28 , 29 , 30 , 31 ]. These intensive bands were also noticed at similar positions in the SVAgNP and the FUAgNP FTIR spectra (1623 and 1605 cm −1 , respectively), but attenuated.…”
Section: Resultsmentioning
confidence: 99%
“…These changes confirmed the involvement of plant extract metabolites in AgNP formation. OH and CO groups present in plant extract play a key role in the reduction and stabilization of NPs …”
Section: Resultsmentioning
confidence: 99%